Strategies for sustainable development – Exploring the similarities and differences between the European Union and the Visegrad Four’s - Kozma Dorottya Edina; Козма Д. Е. (ФОП Сабов А. М., 2019)
Abstract. With the explosive growth of mankind and as a result of the escalating migration wave the European Union attaches greater importance to sustainable development and sustainability. In my study within the European Union, I examine the countries of the Visegrád Four in terms of sustainability. The Visegrád countries (also known as V4) have gone through great changes during the last two decades in case of economic, social and environmental perspectives equally. Incorporationg these factors into their sustainable development strategy and their indicator system has been implemented in different ways which can be seen from the year of the development of the strategies. The four countries are investigating great power in sustainable development, so it is essential to examine how the V4 countries could incorporate and apply the goals of sustainable development (EU SDG) and its indicators into the lives of the citizens and in the policies.
Стратегії сталого розвитку – Вивчення спільних та відмінних рис між Європейським Союзом та країними Вишеградської четвірки
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00007679
Keywords: Visegrád Four; European Union; sustainable development; indicator; indicator system